Application of kinetic pyrolysis models to the analysis of flax chipboards under fire. (June 2022) - Tran, T.T.; Khennane, A.; Khelifa, M.; Girods, P.; Oudjene, M.; Rogaume, Y.
Abstract: This study presents a three-dimensional finite element model to describe the thermomechanical behaviour of flax chipboards under fire conditions. The model is based on kinetic models considering the thermal degradation during the pyrolysis phase and the evolution of the physico-mechanical properties as functions of temperature. The numerical model is integrated into Abaqus via user subroutines (Umat and Umatht) and applied to the analysis of the fire behaviour of panels made of flax chipboards. Thermogravimetric tests are performed on flax particles to serve for the identification of the kinetic parameters of the pyrolysis models. Once these kinetic parameters are determined, they are integrated into a complete numerical model to simulate the behaviour under fire of flax chipboards on small and large scales. The obtained trends in the predicted values indicate good agreements when compared to the measured values. The simulations show that the numerical model is capable of accurately modelling the thermomechanical transfers taking place within the material during exposure to fire.